Fan loyalty as a major determinant for using data analytics in sport sponsorship - Herrouz, Jihene (2022)
Data analytics is a substantial element of today’s marketing communication. Nonetheless, marketers, sponsors and researchers lack a holistic and comprehensive understanding of key determinants for using analytical tools in sports sponsor ship. There is an agreement around the role of data analytics in driving revenues, however researchers do not delve into the sports fan loyalty as major determinant for using data analytics in sport sponsorship. The purpose of this thesis is to understand how the loyalty of the sports consumer should be the driver for organizations to employ data driven strategies. Both qualitative and quantitative methods were applied, through conducting semi-structured interviews with industry experts and an analysis of secondary data collected from company reports. Results suggest that the sports consumer is different than other types of consumers, and that trends in sports sponsorship are driven and influenced by fan loyalty.